Effects of Bodypump Exercise on the Emotions and Life Satisfaction among Women during the Coronavirus Pandemic - Ayed Zureigat; Osama Abdel Fattah; Alaa Elayyan (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2021)
The study aimed to investigate the effect of the Bodypump exercise on women's' emotions and life satisfaction during the coronavirus epidemic. To achieve this, we used the quasi-experimental approach on a sample consist- ing of (34) untrained healthy women, divided into two groups (17) as a control group and (17) as the experimen- tal group. Because of the home quarantine and, in order to face-to-face interaction, we used a questionnaire to measure the emotions and life satisfaction level using the Google Forms web tool. The study tool consisted of 40 paragraphs divided into 20 paragraphs for emotions and 20 paragraphs for life satisfaction. Before applying the experiment, the emotions and life satisfaction were measured among the study sample; next, the experimental group applied the Bodypump exercise programme. Also, the study results have shown that the level of life satis- faction and positive emotions among the two groups came with a low average in the pre-measurement, as well as the emotional stability domain that was the most affected in a negative way through the coronavirus epidemic. Additionally, statistically significant differences existed between the pre and post-measurement in the emotions and life satisfaction among the two groups and in favour of the experimental group.